Analisis Motion Graphic untuk Pemasaran sebagai Fenomena Sosial Baru; Studi Kasus Event Eraspace 2023 - Pratama, Din Eri; Pratama, Bagas Wahyu; Oxygentri, Oky; Ema, Ema (Jurnal Intervensi Sosial dan Pembangunan, 2025)
This research discusses the role of Motion graphics in digital marketing strategies, especially on Instagram, with a case study of the Eraspacetival event. The use of Motion graphics proved effective in attracting audience attention and increasing brand visibility, which had a positive impact on increasing sales and brand loyalty. Through descriptive qualitative methods and Kress and van Leeuwen's multimodality approach, as well as Anstey and Bull's five semiotic elements (linguistic, visual, audio, gestural and spatial), this study identifies how these elements work synergistically in Eraspacetival's Motion content. The results show that persuasive linguistic elements reinforce the message, interactive visuals draw audience engagement, and upbeat sound effects and music enhance interaction. The gestural and spatial elements guide the audience in understanding the flow of information, so the Motion content succeeds in creating significant interaction, evidenced by the increase in likes and comments from the audience.Keywords: Motion Graphic, Marketing Communication, Multimodal, Eraspacetival